2024
DOI: 10.1021/acsphotonics.3c01604
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Imaging of DNA Interactions with 2D Materials

Jenny Sülzle,
Wayne Yang,
Yuta Shimoda
et al.

Abstract: Two-dimensional (2D) materials offer potential as substrates for biosensing devices, as their properties can be engineered to tune interactions between the surface and biomolecules. Yet, not many methods can measure these interactions in a liquid environment without introducing labeling agents such as fluorophores. In this work, we harness interferometric scattering (iSCAT) microscopy, a label-free imaging technique, to investigate the interactions of single molecules of long dsDNA with 2D materials. The milli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…However, our experiments initially often showed signi cantly larger numbers of emission spots than expected at these low biomolecule concentrations. These observations indicated that the freshly exfoliated hBN surfaces could easily become contaminated by other uorescent emitters during sample preparation, which may explain why only a limited number of experimental studies have successfully explored the binding and diffusion of biomolecules on vdWMs including hBN 42 . Therefore, we sought to pinpoint the exact sources of contamination and develop robust protocols for maintaining the purity of surfaces during sample preparation.…”
Section: Dna Adsorption On Hbn Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our experiments initially often showed signi cantly larger numbers of emission spots than expected at these low biomolecule concentrations. These observations indicated that the freshly exfoliated hBN surfaces could easily become contaminated by other uorescent emitters during sample preparation, which may explain why only a limited number of experimental studies have successfully explored the binding and diffusion of biomolecules on vdWMs including hBN 42 . Therefore, we sought to pinpoint the exact sources of contamination and develop robust protocols for maintaining the purity of surfaces during sample preparation.…”
Section: Dna Adsorption On Hbn Surfacesmentioning
confidence: 99%
“…Despite these promising prospects, to date, only few experimental studies have addressed the binding and diffusion of biomolecules on vdWMs at single-molecule resolution 42 . This pursuit has been hindered by the stringent requirements of the surface, which must possess three key properties: (i) optimal binding energy allowing mobility of biomolecules while ensuring prolonged localization, (ii) chemical stability and high cleanliness in aqueous environments, and (iii) no attributes such as uorescence quenching or auto uorescence that could compromise optical measurement techniques including single-molecule uorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of the temporally static background, 'moving average' background subtraction methods, also referred to as temporal filtering, enable signals from single proteins and small protein complexes to be detected in the process of adsorbing onto, desorbing from, or moving along a coverslip [2][3][4][5][6] . With single-molecule sensitivity, iSCAT has proven valuable for measuring the molecular mass and oligomerization states of single biomolecules 2 via mass photometry and for detecting the dynamics of biomolecules such as motor proteins 7 , protein filaments 8 , DNA on two-dimensional materials 9 and viruses and proteins on supported lipid bilayers (SLB) [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of the temporally static background, 'moving average' background subtraction methods, also referred to as temporal filtering, enable signals from single proteins and small protein complexes to be detected in the process of adsorbing onto, desorbing from, or moving along a coverslip. [2][3][4][5][6] With single-molecule sensitivity, mass photomety (MP) has proven valuable for measuring the molecular mass and oligomerisation states of single biomolecules 2 via mass photometry and for detecting the dynamics of biomolecules such as motor proteins, 7 protein filaments, 8 DNA on two-dimensional materials 9 and viruses and proteins on supported lipid bilayers (SLB). [3][4][5] In single-molecule fluorescence studies, strategies have been established to engineer the surface for investigating protein-protein and protein-nucleic acid interactions.…”
Section: Introductionmentioning
confidence: 99%